Die begronding van geregtigheid - 'n Perspektief op die wettebundels van die Pentateug - F. N. Lion-Cachet (In die Skriflig, 1994)
We can ascribe a certain sense of righteousness to all people. Using the legal codes of the Pentateuch (the Book of the Covenant, Deuteronomy and Leviticus-Numhers), this paper undertakes to answer the question of the extent of the code's foundation in God and His relationship with people.